Composite ecological anti-seepage layer and preparation method thereof
Patent Information
- Application Number
- CN202611111639.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-16
AI Technical Summary
[0009]本发明针对现有技术存在的问题,提出一种复合型生态防渗层及其制备方法,解决现有技术防渗性能与截污性能无法协同最大化的问题
1、协同防渗性能大幅提升,减渗效果显著
Smart Images

Figure CN122916336A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of groundwater pollution prevention and control and ecological environment restoration technology, specifically a composite ecological seepage barrier layer and its preparation method. Background Technology
[0002] Groundwater is a vital ecological water resource and a source of water for domestic and industrial use. However, heavy metal pollution is characterized by its insidious nature, delayed effects, difficulty in degradation, and tendency to accumulate. Once it infiltrates groundwater aquifers, it causes long-term, regional damage to soil and water ecosystems, resulting in extremely high remediation difficulties and costs. Constructing a functional seepage-proof intercepting layer between the pollution source and the groundwater aquifer is a core technology for blocking the spread of heavy metal pollution and achieving in-situ soil and water remediation. Currently, the mainstream seepage-proof intercepting technologies in the industry are mainly divided into two categories: microbial biofilm seepage-proof technology and natural environmental material adsorption seepage-proof technology. However, both of these individual technologies have significant technical shortcomings and cannot meet the engineering application needs of complex heavy metal mixed pollution scenarios. Specific shortcomings are as follows: 1. Microbial Induced Calcium Carbonate Precipitation (MICP) Biofilm Leakage Prevention Technology This technology is currently a popular approach in the field of ecological seepage prevention. Its core principle involves using urease-producing microorganisms such as Bacillus pasteurellii to hydrolyze urea substrates in water and the matrix, generating carbonate ions. These carbonate ions combine with calcium ions to form calcium carbonate crystals. The crystals then precipitate and cement the soil and riverbed matrix particles, filling the matrix pores and reducing the media's permeability coefficient, thus achieving seepage prevention. This technology boasts advantages such as being eco-friendly, causing no secondary pollution, and facilitating in-situ construction, and is widely used in soil seepage prevention and reinforcement.
[0003] However, numerous experiments and engineering applications have shown that single MIP biofilm technology has a core drawback: strong selectivity for heavy metal immobilization and poor adaptability to complex pollution. Specifically, calcium carbonate crystals have a poor affinity for Pb. 2+ It possesses extremely strong adsorption and precipitation affinity, and can rapidly generate stable lead carbonate precipitates for fixation, but it has poor affinity for Cd. 2+ Cr 3+ Cu 2+ The immobilization capacity of heavy metal ions is significantly weak. In complex pollution systems with multiple metals coexisting, Pb, with its high affinity, is particularly effective. 2+ It will preferentially occupy the active adsorption sites and precipitation sites on the surface of calcium carbonate crystals, generating a strong competitive adsorption effect, directly leading to Cr 3+ Cd 2+ The migration ability of heavy metals with weak affinity is greatly enhanced.
[0004] The study of soil column leaching test data confirms (see...) Figure 1 Table 1): In a multi-metal complex contaminated system, the matrix after single MIP coating treatment, Cr 3+The penetration time is shortened by 25% compared to a single heavy metal pollution system, and the overall heavy metal interception efficiency decreases by 10%. It cannot achieve synergistic, balanced, and efficient fixation of multiple heavy metals, making it difficult to adapt to complex and compound pollution scenarios such as industrial sites, mines, and rivers.
[0005] 2. Single-environment material adsorption-type seepage prevention technology This technology primarily involves incorporating natural and environmentally friendly materials such as bentonite, kaolin, and humic acid into soil and riverbed substrates. Utilizing the materials' inherent ion exchange, physical adsorption, and complexation reaction properties, it achieves the retention and fixation of heavy metal ions. Simultaneously, by filling the substrate pores, it achieves a seepage prevention effect. This technology is low-cost, uses readily available materials, and has good ecological compatibility, making it a commonly used technique for traditional water and soil pollution control.
[0006] However, this technology suffers from fatal flaws: limited adsorption capacity, poor fixation stability, and insufficient long-term effectiveness. The fixation of heavy metals by single environmental materials primarily relies on physical adsorption and reversible ion exchange, achieving only temporary retention and failing to convert free heavy metals into stable mineral forms. Changes in the external environment, such as temperature, water pH, and water flow, can easily lead to the re-release of adsorbed heavy metals, causing secondary pollution.
[0007] The comparative experimental data show (see...) Figure 2 Table 2): Single Environmental Material Treatment Group (OM) on Pb 2+ The equilibrium adsorption capacity was only 4.99 mg / g, indicating extremely low adsorption capacity; meanwhile, BCR heavy metal speciation analysis showed (see...) Figure 3 (and Table 3), Cd after single material treatment 2+ The proportion of active release forms (F1+F2) is still as high as 34%, posing significant long-term environmental risks and failing to meet the engineering requirements for long-term pollution control of groundwater.
[0008] Currently, there is no mature solution in the industry that precisely couples MIP biomineralization technology with multi-component environmental material adsorption technology. Existing attempts are merely simple mixing and superposition without forming a structured synergistic mechanism. This results in the inability to simultaneously leverage the dual advantages of bio-cementing for seepage reduction and material adsorption for pollution interception. This leads to industry technical pain points such as "incomplete seepage prevention, short-term effectiveness of solid pollution, and poor adaptability to mixed pollution," which are also the core technical challenges that this invention urgently needs to solve. Summary of the Invention
[0009] This invention addresses the problems existing in the prior art by proposing a composite ecological seepage barrier layer and its preparation method, thus solving the problem that the seepage barrier performance and pollution interception performance of the prior art cannot be maximized synergistically.
[0010] This invention is achieved through the following technical solution: A composite ecological seepage barrier layer uses a riverbed or vadose zone matrix as the matrix base layer, and a biofilm rigid skeleton layer is set on the matrix base layer. The pores of the biofilm rigid skeleton layer are filled with multi-component environmental materials to form a flexible filling layer. The biofilm rigid skeleton layer is formed by microbial-induced calcium carbonate to form in-situ precipitation and uniformly cement it to the surface of matrix particles. The multi-component environmental materials include bentonite, kaolin, and humic acid.
[0011] Preferably, the microorganism is Bacillus pasteurellii.
[0012] Preferably, bentonite, kaolin, and humic acid are mixed in a mass ratio of 1:1:1 to form a multi-component environmental material.
[0013] The method for preparing a composite ecological seepage barrier includes the following steps: Step 1: Activation of functional strains and preparation of bacterial solution; Step 2: Prepare an equimolar concentration of urea-calcium chloride cementing solution, and spray the prepared bacterial solution evenly and completely onto the surface of the riverbed or vadose zone matrix to be treated, so that the bacteria can fully adhere to the surface of the matrix particles; then spray an equal volume of urea-calcium chloride cementing solution to complete the cementing and coating process, and obtain a rigid skeleton layer of biological film. Step 3: Multi-component environmental materials are prepared into a slurry, which is then injected into the rigid framework layer of the biofilm through a uniform injection method; Step 4: Overall curing and solidification.
[0014] Preferably, the adhesive coating process is repeated multiple times.
[0015] Preferably, the first step is to select Bacillus pasteurellii, inoculate the cryopreserved strain into a sterile liquid activation medium to complete the strain activation; then transfer the activated strain to a liquid medium containing urea, continue to culture until the logarithmic growth phase of the strain, and collect the bacterial cells by centrifugation.
[0016] Preferably, the conditions for strain activation are: constant temperature 30℃, shaking culture at 180r / min for 24h.
[0017] Preferably, the total concentration of the cementing solution is 1.2~1.6 mol / L.
[0018] Preferably, in step two, after spraying the bacterial solution, the mixture is left to stand for 10-15 hours to allow the bacteria to fully adhere to the surface of the substrate particles.
[0019] Preferably, in step three, a peristaltic pump is used for uniform grouting, with an grouting pressure of 0.05–0.1 MPa (low pressure, lower than conventional soil grouting pressure, to avoid destroying the MICP calcium carbonate thin skeleton, to avoid grout channeling, and to avoid surface bulging); and an grouting flow rate of 3–5 mL / min (uniform low-speed steady-state grouting).
[0020] The beneficial effects of this invention compared to the prior art are as follows: 1. Significantly improved synergistic seepage prevention performance and remarkable seepage reduction effect. This invention combines the macroporous plugging advantages of MICP bio-cement with the microporous filling advantages of composite environmental materials, forming a synergistic seepage reduction effect of "rigid biological framework and flexible material filling," resulting in seepage prevention performance far exceeding that of single technologies. Experimental data shows (see Table 4, ...) Figure 4 The optimal composite seepage barrier of this invention has a saturated permeability coefficient as low as 0.008 cm / min, which is 75.1% lower than that of the original riverbed matrix, and the overall seepage reduction rate can reach more than 90%. Compared with the single bentonite, kaolin, and humic acid material treatment group, the seepage reduction effect is improved by more than 30%. Compared with the single MIP biological membrane treatment group, the seepage reduction effect is improved by more than 20%, completely solving the problem of incomplete seepage prevention by traditional technology.
[0021] 2. Achieves synergistic and balanced immobilization of multiple metals, significantly increasing adsorption capacity. This invention overcomes the selective limitations of single-technology heavy metal fixation by constructing a three-level synergistic control mechanism of "physical barrier—chemical adsorption—mineralization fixation," thereby achieving the control of Pb. 2+ Cd 2+ Cr 3+ Cu 2+ Efficient and balanced immobilization of four typical heavy metals. Data shows that the optimal composite impermeable layer (OIL) described in this invention achieves equilibrium adsorption capacities of 9.97 mg / g, 6.93 mg / g, 3.86 mg / g, and 6.84 mg / g for the four heavy metals, respectively, representing increases of 100%, 76%, 54%, and 66% compared to the single environmental material treatment group. The adsorption capacity is more than doubled, and there are no defects in heavy metal competition inhibition. (Regarding Pb...) 2+ Cd 2+ Cu 2+ Cr 3+ Even in coexisting complex contamination systems, this invention maintains excellent retention performance. In multi-metal complex contamination systems, the weak affinity of Cr... 3+ The cumulative retention efficiency over 30 days can reach 68.4%, which is 25.9% higher than that of the original matrix. It is highly adaptable to complex pollution scenarios and fully demonstrates the robustness of the three-level collaborative mechanism in dealing with complex pollution situations.
[0022] 3. Heavy metals are extremely stable, completely eliminating secondary pollution. This invention achieves a qualitative technological shift in heavy metals, moving from "reversible adsorption and retention" to "irreversible mineralization and fixation." XRD diffraction experiments confirm that after the impermeable layer adsorbs heavy metals, it can stably form inert mineral phases such as cerussite and cadmium carbonate; BCR speciation analysis shows that Pb... 2+The proportion of stable residue state (most stable form) increased to 48%, Cd 2+ Cu 2+ The proportions of active releaseable forms (F1+F2) decreased by 25% and 20% respectively, and heavy metals were permanently fixed within the impermeable layer structure, unaffected by water flow erosion, temperature, or pH fluctuations. This was confirmed by 5-year long-term numerical simulation predictions (see...). Figure 5 This impermeable layer can ensure that the concentration of heavy metals in the groundwater in the area is below the national drinking water safety standard limit for a long time, and has excellent long-term prevention and control performance.
[0023] 4. Excellent ecological compatibility, with no secondary pollution. The Bacillus pasteurellii, bentonite, kaolin, and humic acid used in this invention are all natural and environmentally friendly materials, with no chemical additives, and will not damage the water and soil ecosystem. The impermeable layer retains the natural ecological structure of the matrix, which can maintain the basic ecological connectivity between the water body and the bottom sediment. Unlike the ecological damage of traditional rigid impermeable materials such as concrete and geomembrane, it can be adapted to ecological restoration engineering scenarios.
[0024] 5. Strong process controllability and wide range of engineering applications The preparation process parameters of this invention are standardized and controllable. The microbial culture conditions, cementing solution concentration, construction interval, material ratio, and application dosage have all been optimized through systematic testing. The construction process is simple, in-situ construction is convenient, and no large equipment is required. At the same time, the construction parameters can be flexibly adjusted according to the matrix type, heavy metal pollution concentration, and pollution depth of different sites, making it suitable for water and soil pollution prevention and control projects under different working conditions. It has broad prospects for industrialization and large-scale promotion. Attached Figure Description
[0025] To more clearly illustrate the technical solutions in the embodiments of this disclosure or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0026] Figure 1 This is a penetration curve of heavy metals in a single system; Figure 2 2-a: Adsorption kinetics curves of heavy metals on soil samples with different treatments; 2-b: Adsorption of heavy metals on the blank control soil sample (C) with reaction time; 2-c: Adsorption of heavy metals on the optimal material-infiltrated soil sample (OM) with reaction time; 2-d: Adsorption of heavy metals on the optimal biofilm-coated soil sample (OB) with reaction time. Figure 3 This is a bar chart showing the distribution of heavy metal speciation after leaching. Figure 4 A comparison chart of the osmosis reduction rate of the strain at different times; Figure 5 A 5-year prediction curve of heavy metal concentration in groundwater; Figure 6 This is a scanning electron microscope (SEM) image of the optimal composite ecological impermeable layer (OIL) of the present invention; Figure 7 For optimal composite impermeable layer Pb 2+ Cd 2+ Cr 3+ Cu 2+ Adsorption kinetics curves; Figure 8 Comparison of X-ray diffraction (XRD) patterns of the optimal composite geomembrane before and after adsorption; Figure 9 This is a schematic diagram of the macroscopic structure of the composite ecological seepage-proof layer of the present invention. Detailed Implementation
[0027] To make the technical problems to be solved, the technical solutions, and the beneficial effects of this invention clearer, the invention will be further described in detail with reference to the embodiments and accompanying drawings. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention. The technical solutions of this invention are described in detail below with reference to the embodiments and accompanying drawings, but the scope of protection is not limited thereto. Example 1
[0028] This invention proposes a composite ecological seepage barrier and its preparation method. This seepage barrier relies on a riverbed or vadose zone matrix as a base, and constructs a ternary synergistic dense composite structure from the inside out. The overall structure has no layer gaps and is tightly bonded. The specific layered structure is as follows: The first layer is the matrix base layer, which is the original riverbed or vadose zone natural matrix. It is composed of natural composites of sand, silt, and clay particles, and serves as the bearing foundation of the entire seepage prevention layer. It preserves the natural water and soil ecological structure and ensures ecological connectivity.
[0029] The second layer: MICP biofilm rigid framework layer: calcium carbonate is precipitated in situ through microorganisms (Bacillus pasteurella in this embodiment) and uniformly cemented on the surface of matrix particles. It can block large pores in the matrix, solidify the matrix structure, significantly reduce the basic permeability of the matrix, and at the same time provide an attachment carrier for the outer adsorbent material, solving the problem of loose material being easily lost.
[0030] The third layer is a flexible filling layer of multi-component environmental materials, which is made of bentonite, kaolin and humic acid in a mass ratio of 1:1:1. It is uniformly filled into the micron and nano-scale residual pores of the biofilm skeleton to make up for the leakage defects of the micropores of the biofilm, while providing a large number of ion exchange and complexation adsorption active sites.
[0031] The three-layer structure interlocks and works synergistically to form an integrated ternary dense composite structure of matrix, calcium carbonate skeleton, and environmental materials, simultaneously achieving three core functions: efficient seepage prevention, adsorption of multiple heavy metals, and long-term mineralization and fixation.
[0032] Preparation method of composite ecological seepage barrier layer: This invention employs a step-by-step synergistic preparation process of "first building a rigid framework, then filling with flexible adsorbent material, and finally curing and solidifying the entire process." The parameters are controllable and the operation is standardized. The specific implementation steps are as follows: Step 1: Activation of functional strains and preparation of bacterial culture Sporosarcina pasteurii was selected as the exclusive functional mineralization strain. The cryopreserved strain was inoculated into a sterile liquid activation medium and cultured at a constant temperature of 30℃ and shaking at 180 r / min for 24 h to complete the activation of the strain. Subsequently, the activated strain was transferred to a special liquid medium containing urea and cultured until the logarithmic growth phase of the strain. The bacterial cells were collected by centrifugation and resuspended in sterile physiological saline to prepare a functional bacterial solution with stable concentration for later use.
[0033] Step 2: Preparation of cementitious solution and construction of biofilm substrate Prepare an equimolar concentration of urea-calcium chloride mixed cementing solution with a total concentration of 1.5 mol / L to ensure stable precipitation of calcium carbonate. Evenly and completely spray the prepared bacterial solution onto the surface of the riverbed / vadose zone matrix to be treated, ensuring a single spray completely covers the matrix surface without any liquid accumulation. Allow it to stand for 12 hours to allow the bacteria to fully adhere to the matrix particles. Then, spray an equal volume of urea-calcium chloride cementing solution to complete the single cementing and coating process.
[0034] Repeat the above process of "bacterial solution spraying - standing - cementing solution spraying" for 3 batches to ensure that calcium carbonate crystals precipitate layer by layer and cement evenly, forming a dense and uniformly porous rigid framework substrate of MIP biofilm on the surface of the matrix.
[0035] Step 3: Proportioning and Infilling of Composite Environmental Materials Natural bentonite, kaolin, and humic acid were selected as the core adsorbent materials and precisely mixed in a 1:1:1 mass ratio to obtain a composite environmental material. The total application rate of the material was 1 kg / m³. 2Materials are precisely measured according to the construction area. The composite material is mixed with sterile water to prepare a uniform and stable slurry. A peristaltic pump is used for low-pressure and uniform-speed injection (pressure 0.1MPa; injection flow rate: 3mL / min) to slowly inject the slurry into the surface of the biofilm skeleton, so that the slurry can fully penetrate and fill all the remaining micropores of the calcium carbonate skeleton, without gaps or accumulation.
[0036] Step 4: Overall curing and solidification After the material is immersed, it is left to stand and cure at room temperature for 72 hours to allow the biofilm skeleton to fully integrate and solidify with the environmental adsorption material. At the same time, the heavy metal adsorption sites are activated and the mineralization reaction is prepared, ultimately forming a ternary synergistic composite ecological seepage prevention layer with stable structure and optimal performance.
[0037] Effect verification: Test substrate: Natural riverbed silty sand substrate was selected, sieved to remove large particles of impurities, and air-dried for later use; Test strain: Standard strain of Bacillus pasteurellii; Test heavy metal contamination solution: Prepared with Pb 2+ Cd 2+ Cr 3+ Cu 2+ The mixed heavy metal contaminated liquid was used to simulate the mixed pollution of industrial river water; the test environment was: room temperature 25℃, natural ventilation, and normal environment.
[0038] To fully verify the performance of the composite structure of this invention, four parallel comparative examples were set up. The matrix conditions, test environment, and pollution stress conditions of each group were completely identical, with only the treatment process differing. The specific settings are as follows: Comparative Example 1 (Blank Control Group C): The original natural riverbed silty matrix was used without any biological covering or material modification treatment. Only leveling and compaction were performed. This served as the basic reference group for the experiment.
[0039] Comparative Example 2 (Single Environmental Material Treatment Group OM): Only a 1:1:1 composite material of bentonite, kaolin, and humic acid was used, at a concentration of 1 kg / m³. 2 The surface is modified by applying a certain amount of material, without carrying out the MIP biofilm process, and the seepage prevention and solidification are achieved solely by material adsorption and pore filling.
[0040] Comparative Example 3 (Single Biofilm Treatment Group OB): The MICP biofilm layer was constructed using only Bacillus pasteurellii, 1.5 mol / L cementing solution, and a 3-batch cyclic coating process. No environmental composite materials were applied, and the seepage prevention and solidification were achieved solely by relying on the biomineralized calcium carbonate skeleton.
[0041] Experimental Example 1 The fixed bacterial strain was *Sp. pasteurii*. Gradients of cementitious solution concentration (0.5 mol / L, 1.0 mol / L, 1.5 mol / L, 2.0 mol / L) and cementation intervals (6 h, 12 h, 24 h) were set. All other conditions were the same as in Example 1. The soil seepage reduction rate under different working conditions was tested, and the optimal process parameters were screened (see [link to example]). Figure 4 ).
[0042] Experimental Example 2 Using the optimal ternary composite impermeable layer (OIL) of Example 1 of the present invention, a Pb-containing OIL is prepared. 2+ Cd 2+ Cr 3+ Cu 2+ For a multi-metal mixed contaminated liquid, a continuous adsorption kinetic experiment was conducted from 0 to 1800 min. The changes in the adsorption capacity of the four heavy metals at different time points were recorded, and the parameters of the adsorption kinetic model were fitted (see [reference]). Figure 7 ).
[0043] Experimental Example 3 SEM and energy dispersive spectroscopy were performed on the blank matrix, the single material group, the single biofilm group, and the composite impermeable layer of this invention to observe the microstructure, crystal interlocking morphology, and elemental distribution characteristics (for microstructure characterization, see [link to microstructure characterization]). Figure 6 ).
[0044] Test Example 4 XRD diffraction tests were performed on samples of the composite geomembrane layer of Example 1 of the present invention before and after adsorption of heavy metals. The differences in diffraction patterns were compared to analyze the formation of stable mineral phases and verify the mineralization fixation mechanism (see [link to documentation]). Figure 8 ).
[0045] Experimental Example 5 Based on indoor leaching test data, a numerical simulation model was constructed to predict the Pb concentration under 5-year long-term operating conditions. 2+ Cd 2+ Cr 3+ Cu 2+ Concentration changes of four heavy metals in groundwater environment, and assessment of long-term control effectiveness (see [reference]). Figure 5 ).
[0046] Experimental Results Analysis and Conclusions Figure 1The heavy metal penetration time curves of blank matrix (RB) and single materials (OM, OB, OIL) under single heavy metal pollution systems and multi-metal mixed pollution systems are presented. Combined with the breakthrough time (tb) and half-penetration time (t0.5) data in Table 1, the inherent limitations of single MIP technology can be clearly identified. The overall trend shows that in single heavy metal systems, MIP biofilm (OB) and optimized composite substrate (OIL) have good retention and blocking effects on various heavy metals, with long penetration times and slow leakage rates. However, in multi-metal mixed pollution systems, the competitive adsorption effect becomes significantly more pronounced.
[0047] Among them, Pb 2+ It has the strongest affinity for calcium carbonate crystals, preferentially occupies the coating pores and active sites, and has a strong affinity for Cd. 2+ Cu 2+ Especially Cr 3+ Significant adsorption inhibition was observed. Data shows that Cr in the mixed system... 3+ Breakthrough time was reduced from 8 days to 6 days for a single system, a reduction of 25%, significantly advancing the semi-penetration time and greatly increasing the risk of penetration by weakly affinity heavy metals; Cd 2+ Cu 2+ The retention efficiency decreased simultaneously. These charts visually demonstrate that a single MIP biofilm exhibits severe heavy metal fixation selectivity, making it unsuitable for mixed pollution scenarios. This also serves as the experimental basis for the necessity of introducing multi-component environmental materials to construct a composite synergistic system in this invention.
[0048]
[0049] (2) Figure 2 Analysis of heavy metal adsorption kinetics curves in soil samples with different treatments (corresponding to blank C, single material OM, single coating OB, and composite structure OIL). Figure 2 The adsorption kinetics of four types of samples for four heavy metals throughout the entire process were compared, clearly distinguishing the performance differences between each individual technology and the composite technology of this invention. The blank control group (C) had a well-developed matrix pore structure and no functional adsorption sites, resulting in extremely low adsorption capacity for heavy metals and virtually no pollution retention capacity. The single environmental material group (OM) relied on physical adsorption and ion exchange to immobilize heavy metals, achieving a relatively fast adsorption rate, but its limiting adsorption capacity was limited, and adsorption tended to saturate in the later stages, failing to further improve the solidification effect. The single biofilm group (OB) showed good performance for Pb. 2+ It exhibits excellent adsorption performance, but has limited effect on Cr. 3+ Cd 2+ Its adsorption capacity is significantly weak, and the adsorption of heavy metals is extremely uneven.
[0050] The optimal composite oil-water barrier (OIL) of this invention combines the advantages of both a biomineralized framework and a multi-component adsorbent material. Its adsorption rate and saturated adsorption capacity are significantly superior to all single-treatment groups, and it maintains high-efficiency adsorption performance for all four heavy metals without any obvious adsorption limitations. Experiments demonstrate that the composite system is not a simple superposition of single properties; the biomineralized framework optimizes the pore structure, and the material components provide multiple active sites, resulting in a significant synergistic enhanced adsorption effect. This kinetics verifies the innovation and superior performance of the composite structure.
[0051]
[0052] (3) Figure 3 Bar chart of heavy metal speciation after leaching and Table 3 RAC / IR index analysis Figure 3 The distribution of heavy metal speciation (F1 exchangeable, F2 reduced, F3 oxidized, F4 residual) after leaching of samples with different treatments, combined with the risk assessment coefficient (RAC) and stability index (IR) in Table 3, can be used to quantitatively evaluate the long-term effectiveness and environmental safety of each technology in preventing solid waste pollution. The RAC value represents the risk of active release of heavy metals, and the higher the value, the greater the risk of secondary pollution; the IR value represents the proportion of stable inert speciation, and the higher the value, the stronger the stability.
[0053] Analysis results showed that the blank matrix (RB) had the highest proportion of various active forms of heavy metals and the highest RAC value, indicating that heavy metals are very easily leached and released again by groundwater. While the single-material group (OM) and the single-coating group (OB) could reduce heavy metal activity, their improvement effects were limited. (Cd...) 2+ Cu 2+ The proportion of active form remains high, and there is a risk of continuous leakage under long-term leaching conditions.
[0054] After treatment with the composite impermeable layer (OIL) of this invention, the proportion of the four active heavy metal forms (F1+F2) decreased significantly, while the proportion of the stable inert forms (F3+F4) increased significantly; Pb 2+ Cd 2+ Cu 2+ The RAC values were the lowest among all groups, and the IR values were the best overall. This result fully demonstrates that: single technologies can only achieve temporary retention of heavy metals, while the composite structure of this invention can achieve stable solidification of heavy metals, significantly reducing the ecological risk of heavy metals and solving the core pain points of insufficient long-term stability and easy secondary pollution of existing technologies.
[0055]
[0056] (4) Figure 4 Comparative analysis of osmosis reduction rates under different strains and operating conditions Figure 4The results show that the *Sp. pasteurii* strain selected in this invention exhibits significant osmosis reduction performance. Under the same strain, a 12-hour cementing interval and a cementing solution concentration of 1.5 mol / L are the optimal conditions. Excessively high concentrations can lead to osmotic inactivation of the bacteria, while excessively low concentrations result in insufficient calcium carbonate production. Too short an interval leads to insufficient bacterial adhesion, while too long an interval can cause secondary exposure of the matrix pores. Under the preferred conditions of this invention, a single biofilm coating process can achieve a osmosis reduction rate exceeding 60%, laying a solid foundation for subsequent composite filling and verifying the scientific validity and optimality of the bio-framework process parameters of this invention.
[0057]
[0058] (5) Figure 5 Analysis of 5-year heavy metal concentration prediction curves in groundwater Five-year numerical simulation results show that the seepage prevention structure in the blank group and the single-treatment group fails quickly, and Cr 3+ Weakly bound heavy metals typically show leakage risks exceeding limits after about 1.8 years; however, the composite impermeable layer (OIL) of this invention can prevent Pb from leaking out. 2+ Cd 2+ Cr 3+ Cu 2+ The concentration remained consistently below the national groundwater drinking water standard limit over a long period. This demonstrates that the composite structure of the "biological skeleton + material filling" of this invention can achieve long-term resistance control, and the mineralization fixation mechanism completely solves the defects of traditional technologies such as heavy metal desorption and leakage and insufficient long-term effectiveness, thus possessing the capability for long-term engineering service.
[0059] (6) Figure 6 Microscopic SEM / Electro-spectroscopy analysis of composite impermeable layer SEM microstructure analysis revealed that single-layer biofilms exhibit numerous micron-sized interconnected pores, resulting in a loose and easily leached structure. In contrast, the ternary composite structure of this invention features uniformly cemented matrix particles with calcium carbonate crystals, while bentonite, humic acid, and kaolin flexible materials are tightly integrated to fill the crystal pores, resulting in a dense structure without interconnected gaps. Energy dispersive spectroscopy (EDS) analysis confirmed the uniform distribution of functional elements such as Ca, Al, K, and C, demonstrating a deep coupling between biomineralization products and environmental materials, rather than a simple physical mixture. This microstructural analysis explains the core reason for the high impermeability and stability of the composite geomembrane.
[0060] (7) Figure 7 Analysis of heavy metal adsorption kinetics curves in the optimal composite geomembrane The kinetic curves show that the composite geomembrane of this invention exhibits a pattern of "rapid adsorption in the early stage and slow equilibrium in the later stage" for all four heavy metals, with most adsorption completed within 300 minutes and adsorption equilibrium basically reached within 1200 minutes. Compared with the comparative single-material and single-biofilm groups, the composite system of this invention shows better adsorption of Pb. 2+Cd 2+ Cr 3+ Cu 2+ Both the adsorption rate and equilibrium adsorption capacity were significantly improved, and the affinity for Cr was relatively weak. 3+ There is no significant adsorption inhibition of Cd²+, which completely solves the technical pain points of selective adsorption and competitive antagonism of heavy metals in single MIP technology, and achieves simultaneous and efficient capture of multiple metals.
[0061] (8) Figure 8 Comparative analysis of XRD patterns before and after adsorption XRD pattern comparison confirms that before the composite geomembrane of this invention adsorbs heavy metals, only characteristic diffraction peaks of calcium carbonate and clay minerals are present; after heavy metal adsorption, obvious new diffraction peaks of stable minerals such as cerussite (PbCO3) and cadmium carbonate (CdCO3) appear in the spectrum. This proves that the geomembrane does not rely solely on physical adsorption to fix heavy metals, but rather induces free heavy metals to transform into stable mineral phases through the calcium carbonate co-precipitation interface, achieving a qualitative change from "reversible adsorption and retention" to "irreversible mineralization and fixation," thus eliminating the risk of secondary pollution from a mechanistic perspective.
[0062] Figure 9 This indicates the formation of a ternary synergistic dense composite structure (matrix-calcium carbonate framework-environmental material).
[0063] Combination Figures 4 to 9 Based on all experimental data and characterization results, the following conclusions can be drawn: 1. The preferred biological skeleton preparation parameters of this invention are Bacillus pasteurellii, 1.5 mol / L cementing solution, 12 h interval, and 3 batches of coating process. Compared with traditional strains and conventional processes, the basic seepage prevention performance is significantly improved, and the process stability and adaptability are stronger.
[0064] 2. The "matrix-calcium carbonate skeleton-environmental material" ternary composite structure of this invention solves the problems of single biological membrane pore defects, loose single material structure and low adsorption capacity through microstructure interlocking and synergy, thus achieving a leapfrog improvement in seepage prevention performance.
[0065] 3. The three-level synergistic mechanism of "physical barrier-chemical adsorption-mineralization fixation" constructed in this invention completely overcomes the defects of traditional technologies such as strong selectivity of heavy metal fixation, poor adaptability to complex pollution, and easy secondary release. It can fix a variety of typical heavy metals in a balanced manner.
[0066] 4. The composite seepage barrier can achieve long-term stable service. There is no leakage of heavy metals exceeding the standard within a 5-year simulation cycle. Its ecological safety and engineering durability are far superior to existing technologies, and it has application value in large-scale water and soil heavy metal pollution prevention and control projects.
[0067] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A composite ecological seepage barrier layer, characterized in that, Using a riverbed or vadose zone matrix as the matrix base layer, a biofilm rigid framework layer is set on the matrix base layer, and multi-component environmental materials are filled into the pores of the biofilm rigid framework layer to form a flexible filling layer; the biofilm rigid framework layer is formed by microbial-induced calcium carbonate to form in-situ precipitation and uniformly cemented on the surface of matrix particles; the multi-component environmental materials include bentonite, kaolin, and humic acid.
2. The composite ecological seepage barrier layer according to claim 1, characterized in that, The microorganism in question is Bacillus pasteurellii.
3. The composite ecological seepage barrier layer according to claim 1, characterized in that, Bentonite, kaolin, and humic acid are mixed in a 1:1:1 mass ratio to form a multi-component environmental material.
4. The method for preparing a composite ecological seepage-proof layer according to any one of claims 1-3, characterized in that, Includes the following steps: Step 1: Activation of functional strains and preparation of bacterial solution; Step 2: Prepare an equimolar concentration of urea-calcium chloride cementing solution, and spray the prepared bacterial solution evenly and completely onto the surface of the riverbed or vadose zone matrix to be treated, so that the bacteria can fully adhere to the surface of the matrix particles; then spray an equal volume of urea-calcium chloride cementing solution to complete the cementing and coating process, and obtain a rigid skeleton layer of biological film. Step 3: Multi-component environmental materials are prepared into a slurry, which is then injected into the rigid framework layer of the biofilm through a uniform injection method; Step 4: Overall curing and solidification.
5. The method for preparing a composite ecological seepage-proof layer according to claim 4, characterized in that, The bonding and coating process is repeated multiple times.
6. The method for preparing a composite ecological seepage-proof layer according to claim 4, characterized in that, The first step is to select Bacillus pasteurellii, inoculate the cryopreserved bacterial strain into a sterile liquid activation medium, and complete the bacterial strain activation. The activated strain was then transferred to a liquid culture medium containing urea and cultured until the logarithmic growth phase of the strain. The strain was then collected by centrifugation.
7. The method for preparing a composite ecological seepage-proof layer according to claim 6, characterized in that, The conditions for activating the strain were: constant temperature 30℃, shaking culture at 180r / min for 24h.
8. The method for preparing a composite ecological seepage-proof layer according to claim 4, characterized in that, The total concentration of the cementing solution is 1.2~1.6 mol / L.
9. The method for preparing a composite ecological seepage-proof layer according to claim 4, characterized in that, In step two, after spraying the bacterial solution, let it stand for 10-15 hours to allow the bacteria to fully adhere to the surface of the substrate particles.
10. The method for preparing a composite ecological seepage-proof layer according to claim 4, characterized in that, In step three, a peristaltic pump is used for uniform infusion, with an infusion pressure of 0.05–0.1 MPa and an infusion flow rate of 3–5 mL / min.